1994
DOI: 10.1021/bi00185a030
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Recombinant Chimeric Human Protein C and Activated Protein C Containing the .gamma.-Carboxyglutamic Acid and Trailing Helical Stack Domains of Protein C Replaced by Those of Human Coagulation Factor IX

Abstract: The properties of a recombinant (r) chimeric human protein C (PC) containing replacement of its gamma-carboxyglutamic acid (Gla) and helical stack (HS) domains by those of human coagulation factor IX (fIX) have been examined. Titration with Ca2+ of the divalent cation-induced intrinsic fluorescence quenching of this chimera (r-GDIX/PC) allowed determination of the [Ca2+], of 1.8 mM, required to produce this alteration in 50% of the protein molecules. These values were 0.41 and 0.61 mM for wtr-PC and fIX, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 71 publications
3
11
0
Order By: Relevance
“…This is consistent with results from light scattering experiments with other Gla domain‐containing proteins. Thus the Ca 2+ ‐concentration necessary to induce half‐maximal binding has been determined to be 0.55 m m , 0.9 m m and 1.2 m m for factor IX [32], factor VII [33] and protein C [5], respectively. We have found that the membrane‐binding of intact factor X and Gla–EGF N show about the same Ca 2+ dependence, indicating that Ca 2+ ‐binding to domains other than the Gla domain and the N‐terminal EGF‐like domain does not influence the membrane‐binding properties of factor X.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with results from light scattering experiments with other Gla domain‐containing proteins. Thus the Ca 2+ ‐concentration necessary to induce half‐maximal binding has been determined to be 0.55 m m , 0.9 m m and 1.2 m m for factor IX [32], factor VII [33] and protein C [5], respectively. We have found that the membrane‐binding of intact factor X and Gla–EGF N show about the same Ca 2+ dependence, indicating that Ca 2+ ‐binding to domains other than the Gla domain and the N‐terminal EGF‐like domain does not influence the membrane‐binding properties of factor X.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is bolstered by the observation that the isolated Gla domain can block the reaction, albeit with lower efficiency than the intact chimera. The decreased affinity for EPCR is probably due to the fact that the isolated Gla domain prepared by chymotryptic digestion is not in an optimal conformation (48,49). For instance, Colpitts and Castellino (48) have shown that the aromatic stack, in addition to the Gla domain of protein C, is essential for phospholipid binding.…”
Section: Discussionmentioning
confidence: 99%
“…In the first round, the protein C cDNA was amplified with the sense primer 5Ј-tgcgtggaggagacgtgcGACTTCGAGGAGGCCAAGGA-3Ј (primer 1), which contains 18 bases (lowercase) from the prothrombin Gla domain (coding for residues Cys 17 -Cys 22 ) and starts from the Asp 23 of protein C. The antisense primer 5Ј-CTGCAGGGATCTAGACTAAGGTGCCCAG-CTCTTCTG-3Ј (primer 2) includes the stop codon of protein C (underlined) and contains an XbaI restriction site for cloning purposes. The prothrombin Gla domain was amplified from the PC-PT Gla cDNA using the sense primer 5Ј-CGCTAAGCTTCCATGGCCCGCATC-CGAGGCTT-3Ј (primer 3), which starts at the initiation codon of the prothrombin cDNA (underlined) and contains a HindIII restriction site and the antisense primer 5Ј-cttggcctcctcgaagtcGCACGTCTCCTCCA-CGCACT-3Ј (primer 4), which extends from Gla 16 (Glu 16 ) to Cys 22 and also contains 18 bases from the protein C Gla domain starting at Asp 23 (lowercase). The polymerase chain reaction-amplified DNA fragments were isolated by standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…To test this possibility, we have prepared a chimeric form of protein C in which the entire Gla domain or only the portion from residue 1 to 22 has been exchanged with that of prothrombin in an effort to evaluate the regions of the molecules involved in the PE-dependent activities. Other chimeric proteins with protein C with the Gla domain of factor VII (15) and factor IX (16) have been prepared previously and are known to be active, but these have not been examined for their PE dependence or their ability to interact with protein S.…”
mentioning
confidence: 99%